Crosstalk Between Pheromone Signaling and NADPH Oxidase Complexes Coordinates Fungal Developmental Processes - Schmidt, Sarah; Märker, Ramona; Ramšak, Barbara; Beier-Rosberger, Anna M.; Teichert, Ines; Kück, Ulrich (Frontiers in Microbiology, 2020)
Sexual and asexual development in filamentous ascomycetes is controlled by components of conserved signaling pathways. Here, we investigated the development of mutant strains lacking genes for kinases MAK2, MEK2 and MIK2, as well as the scaffold protein HAM5 of the pheromone response (PR) pathway. All had a defect in fruiting body development and hyphal fusion. Another phenotype was a defect in melanin-dependent ascospore germination. However, this deficiency was only observed in kinase deletion mutants, but not in strains lacking HAM5. Notably, the same developmental phenotypes were previously described for NADPH oxidase 1 (NOX1) mutants, but the germination defect was only seen in NOX2 mutants. These data suggest a molecular link between the pheromone signaling pathway and both NOX complexes. Using data from yeast two-hybrid analysis we found that the scaffolding protein HAM5 interacts with NOR1, the regulator of NOX1 and NOX2 complexes. This interaction was further confirmed using differently fluorescent-labelled proteins to demonstrate that NOR1 and HAM5 co-localize at cytoplasmic spots and tips of mature hyphae. This observation was supported by phenotypic characterization of single and double mutants. The oxidative stress response and the initiation of fruiting bodies were similar in Δham5Δnor1 and Δham5, but distinctly reduced in Δnor1, indicating that the double deletion leads to a partial suppression of the Δnor1 phenotype. We conclude that the PR and NOX1 complexes are connected by direct interaction between HAM5 and NOR1. In contrast, PR kinases are linked to the NOX2 complex without participation of HAM5.